Deformation and Bubble Entrapment of Free Surface Before Axisymmetric Bodies Detaching From Water Fully. (16th July 2019) - Song, X.; Wu, Q. G.; Ni, B. Y.; Chen, H. L.
Abstract : Experiments are presented on the deformation of free surface induced by water exit of axisymmetric bodies, particular at the moment before body detaching from water. A set of experimental apparatus is designed to provide driving force for the bodies. A high-speed camera is adopted to capture the motion and deformation of the free surface. Bodies of various shapes, including a stretched spheroid, a sphere, a circular cone and a combination of cylinder and circular cone, are lifted out of water with different velocities, by using a straight rod attached on the top of models. It is found that free-surface deformation is affected by the moving velocity a lot. Three wake flow or free-surface spike patterns are generated corresponding to different velocities. When the velocity is larger than a critical velocity, cavitation incepts and bubble is entrapped inside the water spike, which changes the flow pattern and shape of the spike. It is aimed to explore the spike phenomenon of free surface and explain the reasons behind it.